Perspectivas teórico-metodológicas de docentes do curso de graduação em Terapia Ocupacional da Universidade Federal de São Carlos: análise qualitativa - Garcia, Rafael Eras (Universidade Federal de São Carlos, 2024)
Occupational Therapy is a relatively young profession that emerged in the early 20th century with the aim of promoting health and well-being through occupation. Since the formal inception of the profession, various authors from different countries and contexts have sought to understand, categorize, and organize both theoretical and practical knowledge, contributing to the professional identity of an occupational therapist. Due to sociocultural and political differences between countries and among diverse groups within the same region, the adoption of theoretical and methodological frameworks varies significantly. Focusing on the investigation of this variability, this thesis aimed to identify and describe the theoretical and methodological frameworks adopted by faculty members of the Department of Occupational Therapy at the Federal University of São Carlos (DTO-UFSCar) in their teaching practices. Specifically, it sought to characterize the academic and professional background of the faculty, how this background influenced the use of theoretical and methodological frameworks in teaching, and the differences and similarities among these frameworks. This research is qualitative, with a descriptive-exploratory design. The sample consisted of seven faculty members from DTO-UFSCar, and data collection was conducted through semi-structured interviews, validated by a group of expert judges. The faculty members' responses were transcribed and analyzed based on seven codes/themes defined for this study, namely: Approaches, Practice Framework, Professional Philosophy, Practice Model, Research and Extension, Frames of Reference, and Professional Theories. The responses, associated with the codes/themes, were subjected to Thematic Content Analysis, with the support of ATLAS.ti® software for the coding process. This software evaluated the frequency (magnitude) with which the seven codes/themes appeared in isolation, their interrelationships (density), and their co-occurrence. Among the results, "Professional Theories" and "Research and Extension" were the most prominent themes, mainly associated with "Approaches," "Professional Philosophy," and "Frames of Reference." The theme "Practice Framework" was one of the least mentioned, which may be related to the fact that the adoption of a structure for professional practice is not unanimously agreed upon among faculty members in the Brazilian context. It is concluded that the results obtained reveal numerous similarities and differences in the adoption and teaching of theoretical and methodological frameworks to occupational therapy students. These results are related to each faculty member's undergraduate and graduate education and previous professional activities.
Theoretical-methodological perspectives of faculty members in the undergraduate Occupational Therapy Program at the Federal University of São Carlos: a qualitative analysis
Keywords: Terapia Ocupacional; Docentes; Ensino; Conhecimento; Prática profissional; Occupational Therapy; Faculty; Teaching; Knowledge; Professional practice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 4. Educação de Qualidade; 3. Saúde e Bem-Estar